Homomorphisms of the algebra of symmetric analytic functions on $\ell_1$ - Chernega, I.V. (Carpathian Mathematical Publications, 2014)
The algebra $\mathcal{H}_{bs}(\ell_1)$ of symmetric analytic functions of bounded type is investigated. In particular, we study continuity of some homomorphisms of the algebra of symmetric polynomials on $\ell_p$ and composition operators of the algebra of symmetric analytic functions. The paper contains several open questions.